PSYCHOLOGICAL COUNSELING IN CONDITIONS OF EXPERIENCING ACUTE STRESS REACTION - Palamarchuk, Olha; Shakhov, Volodymyr (Personality and environmental issues, 2024)
This article presents a theoretical and practical analysis of psychological counseling as an effective tool for assisting individuals experiencing acute emotional crises. It explores the essence of crisis counseling, its methodological foundations, stages, and intervention models. Special attention is given to psychotechnical approaches that facilitate client adaptation to traumatic events, including cognitive-behavioral techniques, emotional response strategies, and the Traumatic Incident Reduction (TIR) technique. The ethical principles of counselor activity and the role of social support in the counseling process are emphasized. The importance of timely psychological intervention is highlighted as a preventive measure against the development of PTSD, improvement of emotional well-being, and restoration of personal equilibrium.